PENGARUH LITERASI DIGITAL GURU TERHADAP EFEKTIVITAS PEMBELAJARAN DI SMK SWASTA SE-KECAMATAN TENJOLAYA - Nurul; Muzhir Ihsan; Acep Nugraha; Ima Rahmawati (Institut Agama Islam Sahid (INAIS) Bogor, 2026)
This study aims to determine the effect of teachers’ digital literacy on the effectiveness of learning at private vocational high schools (SMK) throughout the Tenjolaya subdistrict of Bogor. In this study, a quantitative research method was used, and the numerical data collected were analyzed using simple regression analysis. This study employs a correlational method with non-test techniques, as it aims to determine the correlation between teachers’ digital literacy and the effectiveness of learning. The data collection technique used in this study is a questionnaire. The questionnaire in this study utilizes a Likert scale with five response options, consisting of both positive and negative statements. Based on the t-test value in the regression results, which is 2.541, and since the t-value (2.541) is greater than the critical t-value of 1.660, there is a positive influence between the teacher digital literacy variable (X) and the learning effectiveness variable (Y). Keywords Teachers' digital literacy, learning effectiveness.